The Syrian conflict: Regional dimensions and implications - Kirmanj, Sherko (Penerbit Universiti Utara Malaysia, 2014)
The Syrian conflict which started in March 2011 is well into its third year and its dimensions and implications are steadily moving beyond Syrian borders and the broader Middle East.Syria’s uprising has developed into a civil war between government forces and the opposition, motivated primarily by internal and external actors’ strategic and at times existential interests. This article examines the implications and dimensions of the Syrian crisis for the major actors in the region, including Turkey, Iraq, Iran, Lebanon, the Gulf States, Israel and the Kurds.It argues that pitting a Shiite Iran-Iraq-Syria-Hezbollah axis against a Sunni Turkey-Gulf states axis is the most significant geo-political regional effect of the Syrian crisis. What is more devastating is not the division of the region along sectarian lines but the proxy war between the Shiite and Sunni factions.